Engineering and in vitro evaluation of acid labile cholesterol tethered MG132 nanoparticle fortargeting ubiquitin-proteasome system in cancer - Ghosh, Chandramouli; Gupta, Neha; More, Piyush; Sengupta, Poulomi; Mallick, Abhik; Santra, Manas Kumar; Basu, Sudipta (Chemistryselect, 2016)
In recent years, proteasome has evolved as one of the important alternative targets in cancer chemotherapy. However, selective targeting of proteasome system in cancer cells still remains a major challenge. To address this, a potent peptide based proteasome inhibitor MG132 was chemically conjugated with biocompatible-biodegradable cholesterol by acid cleavable hydrazone linkage. Spherical nanoparticles (MG132-NPs) were engineered from cholesterol-MG132 conjugate. Increased amount of free MG132 was released from these nanoparticles in acidic environment compared to physiological milieu in a slow and controlled manner. These MG132-NPs were taken up by breast cancer MCF7 cells into lysosomes within 6 h. Proteasome system was inhibited by these MG132-NPs leading to stabilization of beta-catenin, cyclin A and cyclin B in HEK-293T cells. Interestingly, MG132-NPs induced much improved cell death in drug resistant MDA-MB-231 cells with insignificant toxicity in healthy cells (HEK293 and L929) even in higher concentration.